PERAN BETA AMILOID PADA GANGGUAN KOGNITIF PENDERITA DIABETES TIPE 2 - Yuliarni Syafrita* (NEURONA, 2010)
INTRODUCTION GERIATRIC DIABETES MELLITUS IS ONE OF THE MAIN HEALTH PROBLEM THE INCIDENCE OF WHICH IS CONTINNOUSLY INCREASING IN WORLDWIDE DIABETIC PATIEN WITH COGNITIVE IMPAIRMENTS WILL HAVE SIGNIFICANT DIFFICULTIES IN TREATING THEIR PROBLEMS INCREASING BLOOD GLUCOSE LEVEL AND DURATION OF SUFFERING DIABETES WILL DETERMINE THE SEVERITY OF THE COGNITIVE IMPAIRMENT